The effects of Labisia pumila extracts on bone microarchitecture of ovariectomized-induced osteoporosis rats: A micro-CT analysis - Effendy N.M.; Khamis M.F.; Shuid A.N. (IOS Press, 2024)
Indexed by WOS/SCOPUS